An upscaled model for elastoplastic behavior of the Callovo-Oxfordian argillite. (August 2019) - Zeng, T.; Shao, J.F.; Yao, Y.
Abstract: In this paper, a micromechanical model is proposed to study the elastoplastic behavior of the Callovo-Oxfordian (COx) argillite. Three scales (i.e., macroscopic, mesoscopic and microscopic) are considered. At the mesoscopic scale, the COx argillite is regarded as a three-phase composite with clay as matrix and calcite and quartz as reinforcements. At the microscale, the clay matrix is a porous medium constituted by clay minerals and interparticle pores. The porous clay is described with an extended Gurson-Tvergaard-Needelman (EGTN) model while the calcite and quartz reinforcements are described with the linear isotropic elastic model. The macroscopic behavior of the COx argillite is determined by adopting the Hill's incremental formulation. All the numerical aspects including: (1) the integration of the EGTN model with the backward Euler method; (2) the derivation of the corresponding consistent tangent moduli from a new point of view; (3) the realization of the homogenization process, are fully described. The proposed micromechanical model is validated from two aspects. The first aspect is the numerical predictions against the finite element (FE) computations performed on a two-phase unit cell, where the key steps related to the modelling are presented. The second aspect is the comparisons between the numerical predictions and experimental data.